Analysis of the propensity to formalize individual microentrepreneurs in the municipality of Salgueiro – PE (Research, Society and Development, 2022)
This work was developed based on the study and knowledge of Complementary Law nº 128/2008, which presents the figure of the Individual Microentrepreneur (MEI), and aims to analyze the propensity of formalization of individual microentrepreneurs in the municipality of Salgueiro-PE, verifying why entrepreneurs opt for such a regime. The methodology consists of a questionnaire that was answered by 67 entrepreneurs who are served in the entrepreneur's room in the municipality of Salgueiro-PE. This work is characterized by its descriptive nature, which in turn describes the characteristics of certain populations, and the approach to the problem presented was developed through quantitative means. The data obtained were treated with Excel Software and the most relevant results showed that: the gender was 61.2% men and 38.8% women, the age group that stood out was 31 to 40 years old and the level of education 41.8% of respondents had completed high school. The main reasons for opting for formalization were: access to social security rights (35.8%), ease in the opening process (28.4%) and concern with inspection (16.4%). Addressing the disadvantage, the main conclusions were that there were no disadvantages (53.7%) followed by low billing margin (22.4%).